Evaluation of agrochemicals and bioinputs for sustainable bean management on the Caribbean coast of Colombia (2015)
The sustainable expansion of bean cultivations requires technologies that do not limit their phyto-recovering properties. Therefore, the objective of this study was to propose agronomic management of conservation for bean cultivation considering the microbiological characteristics of two mega-environments of the Colombian Caribbean coast and the compatibility between agrochemicals and bioinputs. The methodology included rhizospheric microbe population counts, identification of phytopathogenic fungi in plant tissues and soils, compatibility studies of pesticides with biocontrollers, and determination of residual contents of pesticides in bean seeds. The microbial populations corresponded to those previously registered for the lower tropics, but with quantitative differences in the genera. Phytophthora, Colletotrichum and Fusarium were registered in the humid Caribbean, while Colletotrichum and Curvularia affected crops in the dry Caribbean. The Beauveria bioinput was not compatible with the evaluated agrochemicals, while Trichoderma was compatible with chlorpyrifos, thiabendazole and oxycarboxin. Metarhizium was compatible with glyphosate and oxycarboxin at 10% of the recommended dose. Lindane residues were found in the beans harvested at three of the studied locations. The combined use of agrochemicals and bioinputs on bean crops is feasible as long as the time of application of the latter is made according to the half-life of the chemical and the organic matter content of the soil is increased.